ECTOPIC PREGNANCY - A NEW LOOK AT THE PROBLEM - Tuksonova D.I (Scholar Express Journals, 2023)
Repeated ectopic pregnancy and fertility disorders in the future. According to one study, the incidence of pregnancy after conservative or surgical treatment of ectopic pregnancy was 80%, and the average time interval before conception was 9-12 months, and fertility after wait–and-see tactics and surgical treatment was the same. Ectopic pregnancy increases the risk of developing such a condition in the future by 7-13 times. This means that in 50-80% of cases, the next pregnancy will be uterine and in 10-25% – ectopic. All patients with ectopic pregnancy should be informed about the increased risk of its occurrence in the future.
Keywords: Ectopic pregnancy; hysteroscopy; trophoblast implantation; fallopian tubes